Penelitian Feminis dalam Kajian Budaya:Titik-Temu dan Kontribusi - Christian Budiman; Christian Budiman (Jurnal Kawistara, 2021)
Gender studies have generated a perspective called feminist research that is not merely research on women, but also research for women. Driven by a will to prioritize women’s experiences and, therefore, the aim to emphasize the importance of their subjective experiences, feminist researchers tend to apply qualitative research methods by placing great emphasis on women as subjects of knowledge. The differences in disciplinary backgrounds and the methodological and epistemological positions of feminist are also increasingly blurred by the mutual borrowing of concepts and thoughts across disciplines, especially from literary theory, history, and cultural studies. In cultural studies, with its recent development recently, feminist research tends to be more oriented towards the basic assumptions of poststructuralism and/or postmodernism. They reject the perspective of a monolithic woman so that, therefore, there is no single and unitary truth about the story of woman’s reality. In this regard, culture is an important issue on the academic and political agenda of feminists. Not only is culture inseparable from gender and power factors, but it can also produce a better understanding of subjectivity. By understanding gender specifically as discourse, they do not deny the possibility of female subjectivity that is multiple, fragmented, and open up opportunities for differences and variations. Compared to the other feminist research positions, feminist cultural studies seem more hybrid, radical, and subversive.